Prevalence and Characterization of Multi-Drug-Resistant Gram-Negative Bacilli Isolated From Lebanese Poultry: A Nationwide Study - Dandachi, Iman; Sokhn, Elie S.; Dahdouh, Elias A.; Azar, Eid; El-Bazzal, Bassel; Rolain, Jean-Marc; Daoud, Ziad (Frontiers in Microbiology, 2018)
Currently, antimicrobial resistance is one of the most prominent public health issues. In fact, there is increasing evidence that animals constitute a reservoir of antimicrobial resistance. In collaboration with the Lebanese Ministry of Agriculture, the aim of this study was to determine the prevalence of intestinal carriage of multi-drug-resistant Gram-negative Bacilli in poultry farms at the national level. Between August and December 2015, 981 faecal swabs were obtained from 49 poultry farms distributed across Lebanon. The swabs were subcultured on MacConkey agar supplemented with cefotaxime (2 μg/ml). Isolated strains were identified using MALDI-TOF mass spectrometry. Multilocus sequence typing analysis was performed for Escherichia coli. Phenotypic detection of extended spectrum beta lactamases and AmpC production was performed using double disk synergy and the ampC disk test, respectively. Beta lactamase encoding genes blaCTX-M, blaTEM, blaSHV, blaFOX, blaMOX, blaEBC, blaACC, blaDHA and blaCMY using PCR amplification. Out of 981 faecal swabs obtained, 203 (20.6%) showed bacterial growth on the selective medium. Of the 235 strains isolated, 217 were identified as E. coli (92%), eight as Klebsiella pneumoniae (3%), three as Proteus mirabilis (1%) and three as Enterobacter cloacae (1%). MLST analysis of E. coli isolates showed the presence of ST156, ST5470, ST354, ST155 and ST3224. The phenotypic tests revealed that 43.5%, 28.5% and 20.5% of the strains were ampC, ESBL and ampC/ESBL producers, respectively. The putative TEM gene was detected in 83% of the isolates, SHV in 20%, CTX-M in 53% and CMY ampC beta lactamase gene in 65%. Our study showed that chicken farms in Lebanon are reservoirs of ESBL and AmpC producing Gram-negative bacilli. The level of antibiotic consumption in the Lebanese veterinary medicine should be evaluated. Future studies should focus on the risk factors associated with the acquisition of multi-drug-resistant organisms in farm animals in Lebanon.